STAGES OF RESETTLEMENT OF ECO-MIGRANTS OF ADJARA REGION AND STATE STRATEGY (ON THE EXAMPLE OF GURIA REGION) - Zoidze, Ineza; Irakli Manvelidze; Levan Jackeli; Natalia Lazba; Irine Tsintsadze (International Journal of Innovative Technologies in Social Science, 2022)
The modern migration processes in Georgia, especially ecological motives that are caused by the social enviroment have many reasons and they don’t fully corresponds to the socio-economic strategic interests of the development of the country. It is the weak economy mainly due to geographical factors, the backwardness and high cost of the service sector, and the dangerous natural processes that periodically put the need for intensive one-way migration on the agenda. Based on this, the purpose of the study is to determine the nature and stages of ecomigration of the population from the Ajara region at different times in the context of the state strategy, on the example of the ecomigrants settled in the Guria region. In order to achieve the mentioned goal and to study the issue, the institutional approach to the study of migration processes is used. The research is based on quantitative and qualitative social research techniques, as well as analysis and statistical methods. All this helped us in proper analysis and study of collected primary and secondary scientific information and materials. The survey was conducted from March 12 to September 25, 2022. According to the results of the research, in the presented material, the stages of eco-migration from the Adjara region to the Guria region are studied for the first time, its nature is determined, the state policy and its characteristics are evaluated, and various problems related to eco-migration are described. Also, during the research process, we developed recommendations that will contribute to the effectiveness of the state eco-migration policy. Based on the set goal of the research problem and the research issues, the research included the study of the scientific literature surrounding the research problem, the study of state documents, including archival documents, press and media materials, and the implementation of field research in the areas inhabited by ecomigrants.